Treatment Outcomes in Septic Arthritis of the Foot and Ankle in People Who Inject Drugs. Issue 3 (30th July 2020) - Shields, Margaret V.; Toppo, Alexander; Menendez, Mariano E.; Tybor, David; Dewire, Peter; Wurcel, Alysse; Salzler, Matthew
Background: Although injection drug use (IDU) is a known risk factor for septic arthritis (SA) of the foot and ankle (F&A), disease and hospitalization outcomes are poorly characterized. We evaluated national trends, demographic characteristics, and hospitalization outcomes of SA of the F&A in people who inject drugs vs those who do not. Methods: Using the Nationwide Inpatient Sample, we identified all patients aged 15-64 with a principal discharge diagnosis of SA of the F&A from 2000 to 2013 and evaluated if they were related or unrelated to IDU. We assessed differences in demographic characteristics and in-hospital outcomes in these groups. Results: From 2000 to 2013, there were an estimated 14, 198 hospitalizations for SA of the F&A in the United States, and 11% were associated with IDU (SA-IDU). Compared to SA unrelated to IDU, people with SA-IDU were significantly more likely to be younger, black, and have Medicaid or no insurance. People with SA-IDU were significantly more likely to leave against medical advice (9.7% vs 1.4%, P < .001), have a longer length of stay (9.2 vs 6.8 days, P < .001), and incur increased hospital charges ($58 628 vs $38 876, P = .005). People with SA-IDU were significantly less likely to receive an arthroscopy (1.5% vs 6.5%, P < .001) or arthrotomy (2.2% vs 11.0%, P < .001) of the foot. Conclusion: People with SA-IDU of the F&A had suboptimal hospitalization outcomes with greater costs. Recognizing risk factors and proactively addressing potential complications of substance use disorder in the hospital should be prioritized by the orthopedic community. Level of Evidence: Level III, retrospective cohort study.